The Latin American Observatory of Population Censuses Experience: Increasing Statistical Literacy through an Academia-Civil Society Network - Mendes Borges, Gabriel (2024)
Governments around the globe count their population. They have been known since almost five thousand years ago, from the dawn of organized societies (Grajalez, Magnello, Woods, & Champkin, 2013), and nowadays, countries conduct them around every ten years. Likewise, censuses have historically been fundamental for the state, science, and civil society. Today’s cornerstone of statistical systems provides essential information for developing small area knowledge, sample frameworks for specialized surveys, and securing considerable technological and methodological investment in official statistics. Despite the innovations in different information systems, such as alternative methods of demographic data, the relative ease of access, and specialized studies, modern censuses still represent a unique and powerful tool in Latin America to quantify and investigate demographic, social, and economic facts toward providing invaluable knowledge about population structure and dynamics. Users exploit census results, assuming they are valid and reliable due to homogenous and technical procedures. This traditional approach to census data has two limitations: first, it usually disregards the extra-statistical elements of the census, that is, its preparation, (political) contingencies, and additional technical factors that affect the outcomes; and second, even if users go beyond a purely instrumental approach to census results and pay attention to the socio-political context of their production, they generally analyze production processes in a framework of methodological nationalism, that is, neglecting the possibility of studying them across countries or regions. Usually, we understand population censuses as tools utilized by state agencies where governments extract information that later is employed to design public policies. As we know from valuable contributions such as Desrosières (2012) and Emigh, Riley, and Ahmed (2016), the census bases its definitions on social realities, and the outcomes are co-produced by societies. How are censuses interpreted in spaces that are not academia or government? This chapter describes the experience of a project developed to minimize these limitations with a transdisciplinary tactic. The Latin American Observatory ofPopulation Censuses (OLAC) was formed in 2015 to analyze Latin American censuses’ technical and non-technical matters. We describe its experience contributing insights that divulge what is frequently missing when we observe censuses in an isolated and exclusively statistical way by displaying the point of view of a third party that documents and analyzes the heterogeneity of population censuses regarding the social actors involved. At the same time, the initiative shows that there are open spaces in the Global South to discuss ideas about the census in conversational ways. The rest of this chapter divides into three sections. First, we synthesize the conceptual corpus from where the Observatory develops. Second, we describe the project’s historical context and to which part of the literature it contributes and explains the mission accomplishments after seven years of work. Finally, we depict the crisis we faced during the 2020 census round, closing these thoughts with theoretical and practical questions for the future.